PENGARUH TEKNIK ROLE PLAYING TERHADAP SIKAP TANGGUNG JAWAB PADA SISWA KELAS XI - Ruhil Kusmawati; Farida Herna Astuti; Khairul Huda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Responsibility is an important character trait that needs to be developed in students because it is closely related to discipline, commitment to tasks, and awareness in carrying out learning responsibilities. However, in educational practice, there are still students who demonstrate low levels of responsibility, such as failing to complete assignments on time and showing a lack of compliance with school regulations. One approach that can be used to help develop this attitude is group guidance using the role playing technique, which provides students with opportunities to understand various social situations through role-playing activities. This study aims to determine the effect of the role playing technique on improving the responsibility attitudes of eleventh-grade students at SMAN 7 Mataram in the 2021/2022 academic year. This research employed a quantitative approach with a one group pre-test–post-test design. The population consisted of 41 students, while the sample included 7 students who had low levels of responsibility and were selected using purposive sampling. Data were collected using a questionnaire and analyzed using a paired sample t-test to determine the difference between scores before and after the treatment. The results of the analysis showed that the calculated t-value (5.474) was higher than the t-table value (2.447) at a 5% significance level with 6 degrees of freedom. Based on these findings, it can be concluded that the application of the role playing technique in group guidance has a significant effect on improving the responsibility attitudes of eleventh-grade students at SMAN 7 Mataram. ABSTRAK Sikap tanggung jawab merupakan salah satu karakter penting yang perlu dikembangkan pada siswa karena berkaitan dengan kedisiplinan, komitmen terhadap tugas, serta kesadaran dalam melaksanakan kewajiban belajar. Namun dalam praktik pendidikan masih ditemukan siswa yang menunjukkan tingkat tanggung jawab yang rendah, seperti tidak menyelesaikan tugas tepat waktu dan kurang mematuhi aturan sekolah. Salah satu pendekatan yang dapat digunakan untuk membantu mengembangkan sikap tersebut adalah layanan bimbingan kelompok dengan teknik role playing, yang memberikan kesempatan kepada siswa untuk memahami berbagai situasi sosial melalui kegiatan bermain peran. Penelitian ini bertujuan untuk mengetahui pengaruh teknik role playing terhadap peningkatan sikap tanggung jawab siswa kelas XI di SMAN 7 Mataram Tahun Pelajaran 2021/2022. Penelitian ini menggunakan pendekatan kuantitatif dengan desain one group pre-test–post-test. Populasi penelitian berjumlah 41 siswa, sedangkan sampel penelitian terdiri dari 7 siswa yang memiliki tingkat tanggung jawab rendah dan dipilih menggunakan teknik purposive sampling. Data penelitian dikumpulkan melalui angket dan dianalisis menggunakan uji paired sample t-test untuk mengetahui perbedaan skor sebelum dan sesudah perlakuan. Hasil analisis menunjukkan bahwa nilai t-hitung sebesar 5,474 lebih besar dibandingkan dengan nilai t-tabel sebesar 2,447 pada taraf signifikansi 5% dengan derajat kebebasan 6. Berdasarkan hasil tersebut dapat disimpulkan bahwa penerapan teknik role playing dalam layanan bimbingan kelompok berpengaruh signifikan terhadap peningkatan sikap tanggung jawab siswa kelas XI di SMAN 7 Mataram.